An Integrated Analysis Reveals Geniposide Extracted From Gardenia jasminoides J.Ellis Regulates Calcium Signaling Pathway Essential for Influenza A Virus Replication - Zhou, Lirun; Bao, Lei; Wang, Yaxin; Chen, Mengping; Zhang, Yingying; Geng, Zihan; Zhao, Ronghua; Sun, Jing; Bao, Yanyan; Shi, Yujing; Yao, Rongmei; Guo, Shanshan; et al. (Frontiers in Pharmacology, 2021)
Geniposide, an iridoid glycoside purified from the fruit of Gardenia jasminoides Ellis, has been reported to possess pleiotropic activity against different diseases. In particular, geniposide possesses a variety of biological activities and exerts good therapeutic effects in the treatment of several strains of the influenza virus. However, the molecular mechanism for the therapeutic effect has not been well defined. This study aimed to investigate the mechanism of geniposide on influenza A virus (IAV). The potential targets and signaling pathways of geniposide in the IAV infection were predicted using network pharmacology analysis. According to the result of network pharmacology analysis, we validated the calcium signaling pathway induced by IAV and investigated the effect of geniposide extracted from Gardenia jasminoides Ellis on this pathway. The primary gene ontology (GO) biological processes and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways KEGG enrichment analysis indicated that geniposide has a multi-target and multi-pathway inhibitory effect against influenza, and one of the mechanisms involves calcium signaling pathway. In the current study, geniposide treatment greatly decreased the levels of RNA polymerase in HEK-293T cells infected with IAV. knocking down CAMKII in IAV-infected HEK-293T cells enhanced virusRNA (vRNA) production. Geniposide treatment increased CAMKII expression after IAV infection. Meanwhile, the CREB and c-Fos expressions were inhibited by geniposide after IAV infection. The experimental validation data showed that the geniposide were able to alleviated extracellular Ca2+ influx, dramatically decreased neuraminidase activity and suppressed IAV replication in vitro via regulating the calcium signaling pathway. These anti-IAV effects might be related to the disrupted interplay between IAV RNA polymerase and CAMKII and the regulation of the downstream calcium signaling pathway essential for IAV replication. Taken together, the findings reveal a new facet of the mechanism by which geniposide fights IAV in a way that depends on CAMKII replication.